Impact of Initial Bulk‐Heterojunction Morphology on Operational Stability of Polymer:Fullerene Photovoltaic Cells. Issue 6 (30th January 2019) - Limbu, Saurav; Pont, Sebastian; Doust, Alexander B.; Kwon, Sooncheol; Fuller, Patrick; Tan, Ellasia; Durrant, James R.; Kim, Ji‐Seon
Abstract: Controlling initial bulk‐heterojunction (BHJ) morphology of photoactive layer is critical for device efficiency of organic photovoltaic (OPV) cells. However, its impact on performance, specifically long‐term operational stability is still poorly understood. This is mainly due to limitations in direct measurements enabling in situ monitoring of devices at a molecular level. Here, a thermal annealing preconditioning step is utilized to tune initial morphology of model polymer:fullerene BHJ OPV devices and molecular resonant vibrational spectroscopy to identify in situ degradation pathways. Direct spectroscopic evidence is reported for molecular‐scale phase‐segregation temperature ( T PS ) which critically determines a boundary in high efficiency and long operational stability. Under operation, initially well‐mixed blend morphology (no annealing) shows interface instability related to the hole‐extracting layer via de‐doping. Likewise, initially phase‐segregated morphology at a molecular level (annealed above T PS ) shows instability in the photoactive layer via continuous phase‐segregation between polymer and fullerenes in macroscales, coupled with further fullerene photodegradation. The results confirm that a thermal annealing preconditioning step is essential to stabilize the BHJ morphology; in particular annealing below T PS is critical for improved operational stability while maintaining high efficiency. Abstract : Operational stability of polymer:fullerene based organic solar cells depends on their initial bulk‐heterojunction morphology. Both extremes (well‐mixed vs phase‐segregated) show instability; the former caused by interlayer degradation and the latter by further macroscale phase‐segregation coupled with fullerene photodegradation. Thermal annealing below molecular‐scale phase‐segregation temperature is critical to maintain well‐mixed morphology with stable interface for optimized efficiency and operational stability.